A decolonial critique of 'authentic' pleasure in contemporary Australian heteroporn. Issue 2 (3rd April 2022) - Gregory, Tim
ABSTRACT: Authenticity in new wave heteroporn is characterized by a commitment to ethical and transparent production, diversity, and mutual pleasure. Lightsouthern is a contemporary new wave Australian porn producer claiming to capture 'authentically sexy Aussie experience'. This article examines Lightsouthern's statements, behind-the-scenes videos, interviews, and contracts to reveal how authentic pleasure is constructed and contrasted to 1990s Australian heteroporn. The article positions Lightsouthern's representation of 'real', inclusive pleasures as an evolution of the co-development of settler sexuality and pornography. Lightsouthern's commitment to transparency and diversity are specific neocolonial strategies that represent settler pleasure as harmonious, unproblematic, and inclusive. Two examples of potentially decolonial pornography, NDNGirls.com and Fuck the Fascism, are analyzed to expose the problems of 'real' pleasure in settler heteroporn. The article argues that depoliticizing pleasure to markers of authenticity, inclusivity, and diversity in settler heteroporn masks the ongoing role of settler sexuality and pornography in denying Indigenous desires, representation, and futures.